The Incidence of Rent Subsidies: Evidence on Rents, Housing Choices and Supply - Essi Eerola; Teemu Lyytikäinen; Tuukka Saarimaa; Tuuli Vanhapelto (CESifo GmbH, 2024)
This paper asks whether, and under which circumstances, rent subsidies to low-income households increase rents. We utilize a reform in Finland that caused large quasi-random variation in housing allowances. We find that large increases in allowances for affected housing units had little or no effect on their rents relative to other units. Thus, the incidence of the reform was on allowance recipients. The reform led to only small changes in recipients' housing choices, and at most modest changes in rental supply. Rent subsidies can be effective even in supply-constrained contexts, if housing choices are unresponsive to the subsidy.
Keywords: H22; R28; 330; housing allowance; rent subsidy; incidence; housing demand; housing supply